High-resolution computed tomography manifestations of COVID-19 infections in patients of different ages. Issue 126 (May 2020) - Chen, Zuhua; Fan, Hongjie; Cai, Jian; Li, Yunjiang; Wu, Baoliang; Hou, Yanchun; Xu, Shufeng; Zhou, Fei; Liu, Yongguang; Xuan, Weiling; Hu, Hongjie; Sun, Jihong
Highlights: GGO with crazy-paving patterns or interlobular septa thickening were common signs. Fewer lesions were identified in the younger and adolescent age groups. Distribution of lesions in the lungs showed age-related differences. Abstract: Purpose: We aimed to compare chest HRCT lung signs identified in scans of differently aged patients with COVID-19 infections. Methods: Case data of patients diagnosed with COVID-19 infection in Hangzhou City, Zhejiang Province in China were collected, and chest HRCT signs of infected patients in four age groups (<18 years, 18–44 years, 45–59 years, ≥60 years) were compared. Results: Small patchy, ground-glass opacity (GGO), and consolidations were the main HRCT signs in 98 patients with confirmed COVID-19 infections. Patients aged 45–59 years and aged ≥60 years had more bilateral lung, lung lobe, and lung field involvement, and greater lesion numbers than patients <18 years. GGO accompanied with the interlobular septa thickening or a crazy-paving pattern, consolidation, and air bronchogram sign were more common in patients aged 45–59 years, and ≥60 years, than in those aged <18 years, and aged 18–44 years. Conclusions: Chest HRCT manifestations in patients with COVID-19 are related to patient's age, and HRCT signs may be milder in younger patients.